New lives for dead houses: urban living and it´s perspectives (Gaceta Técnica, 2023)
Venezuelan migration in recent times has resulted in the abandonment of cities and the loss of effective use of many buildings, producing a hollowing out that we have called "urban osteoporosis." This has meant substantial changes in urban dynamics and the real estate sector. In this article, experiences of emptying cities in the world are reviewed and some options are explored to reuse the Venezuelan urban inventory
Keywords: urban emptying; urban heritage; migrations; Venezuelan diaspora; urban osteoporosis